(3GdefJbi ef cJGH GdJbhis - (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf Hf bjS, CHh HcQ, GHf CHj GdOfjG GdbQTj , J (B281 (3g` s
(3ChdgG (B:s
(3Yf CfS Hf eGdc QVi Gddg Yfg bGd (B: (3SeYJ QShd Gddg Udi Gddg Ydjg hSde (B: (3jbQC (B( (3heG JTGDf EdG Cf jTGA Gddg gh Cgd GdJbhi hCgd GdeZaQI (B) (3abGd QShd Gddg Ydjg GdSdGe (B: (3jbhd Gddg QHce s
(3BNQgG (B:s
(3aEf gGOe GddPGJ hEf ef dGjPcQ ef BHGFg ajeG Hjf BOe EHGMjkG deYQb dg ai GdehcH hGdMeO ddg QH GdYGdejf s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3EfJbGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B131s
Keywords: (3GdJUha hGdBOGH GdTQYjIs